Modulation of insulinlike growth factor I binding to human fibroblast monolayer cultures by insulinlike growth factor carrier proteins released to the incubation media. - De Vroede, M A (1986)
The relative contributions of type I and type II insulinlike growth factor (IGF) receptors and IGF carrier proteins to the binding of IGF-I tracer to cultured human fibroblasts were determined in competitive binding experiments that used unlabeled insulin and synthetic insulin-IGF-I hybrid molecules containing the A chain of insulin and the B domain of IGF-I. Whereas insulin binds only to type I IGF receptors, the B-IGF-I hybrids bind to type I receptors and IGF carrier proteins but not to type II receptors. In suspended human fibroblasts, IGF-I tracer binds predominantly to type I IGF receptors (inhibition by IGF-I much greater than insulin greater than B-IGF-I hybrid molecules). By contrast, in fibroblast monolayers, IGF-I binding was minimally inhibited by insulin or hybrid molecules, suggesting predominant binding to the type II IGF receptor. The type I receptor appears to be masked on fibroblast monolayers, and to require suspension or detergent solubilization of the cells to be demonstrated. In the course of the monolayers binding experiments, we noted that low concentrations of unlabeled IGF-I (5-10 ng/ml) or B-IGF-I hybrids (100 ng/ml) paradoxically increased IGF-I tracer binding up to twofold. We postulated that during the binding incubation (5 h, 15 degrees C), IGF-I tracer partitioned between binding sites on the cell surface and IGF carrier proteins released to the incubation media. Preferential occupancy of binding sites in the media by unlabeled ligand increased the tracer available to bind to the cells. In support of this hypothesis, carrier proteins were demonstrated in the media at the end of the binding incubation with fibroblast monolayers, and the concentration of unsaturated binding sites in the media correlated inversely with tracer binding to the cells. Thus carrier proteins released to the media during the binding incubation modulate the binding of IGF-I tracer to cell receptors, suggesting that the carrier proteins may play an important role in regulating cellular responsiveness to the IGFs.